Molecular dynamics simulation of ionic liquid electrospray: Microscopic presentation of the effects of mixed ionic liquids. (January 2022) - Zheng, Weijie; Liu, Xuhui; Zhang, Jinrui; Cheng, Yufeng; Wang, Weizong
Highlights: MD simulation of electrospray with mixed ionic liquids for the first time. Mixing of ionic liquids changes the emission mode of electrospray. Mixing of ionic liquids reduces onset voltage and increases the stability of electrospray emission. Simple mass ratio empirical approach underestimates electrospray propulsive performance. Abstract: Micro-propulsion devices based on electrospray have advantages of high specific impulse, high precision and compact structure, and are able to meet the requirements of gravitational wave detection and other drag-free spacecrafts for micro-propulsion system. For electrospray thrusters, ionic liquid is the preferred propellant because of its low volatility, high electrical conductivity and thermal stability. Most of the studies presented today focus on single ionic liquid, while the properties of single ionic liquid are certain, which leads to a limitation of electrospray characteristics and hence propulsion performance. Mixing different kinds of ionic liquids broadens the properties of ionic liquids, and thus adjusts the characteristics of electrospray to meet the requirements of diversified space missions. In this paper, the effects of mixing two typical ionic liquids, 1-ethyltrimethylimidazole dicyanamide (EMIM-N(CN)2) and 1‑butyl‑trimethylimidazolium hexafluorophosphate (BMIM-PF6), on propellant properties and electrospray characteristics are investigated by molecular dynamics simulation and validated by comparing with experimental data. The result shows that the mixed ionic liquid changes the emission mode of electrospray thruster. Compared with BMIM-PF6, the specific impulse and thrust for the 50:50 (by mass) mixture increases by more than half of the difference between the two before mixing. In addition, the analysis shows that the range of extrusion voltage is widened by adjusting the mixing ratios to meet the mission requirements for certain specific impulse and thrust.